Selection of economical schemes heat recovery cogeneration power plant - Тодорцев, Юрий Константинович; Тарахтий, Ольга Сергеевна; Бундюк, Анатолий Николаевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper considers several schemes of flue gas heat recovery in a cogeneration plant based on the gas turbine engine. We have considered two types of schemes: those that include only an HRSG for utilizing flue gas heat and schemes supplied with a gas air heater for post-compressor air heating. A coefficient of fuel heat utilization was accepted as a major indicator of the power plant efficiency. We have calculated efficiency indicators of a cogeneration plant to select a recovery scheme of maximum efficiency. The indicators prove the importance of utilizing flue gas heat for heating air after the compressor. The post-compressor increase of air temperature allows reduction of fuel consumption. Therefore, flue gas heat after a gas turbine should be used primarily for heating air after the compressor, and only later it can be utilized in a recovery boiler. The calculations result in a conclusion that the most economical recovery scheme suggests using successively a gas air heater and an HRSG. Such a heat scheme has the lowest fuel flow (qт=0.229 kg/s) and maximum efficiency (ηccpp=0.9122).